Assessment of Knowledge of Senior Dental Students of Isfahan University of Medical Sciences on Medical Emergencies - Elham Faghihian; Zahra Saied-Moallem; Nafiseh Zare (Isfahan University of Medical Sciences, 2022)
Medical emergencies during dental treatment are likely to occur. The ability of a dentist to manage medical emergencies requires sufficient knowledge and information. The purpose of this study was to survey the level of knowledge of the undergraduate dental students of Isfahan University of Medical Sciences on medical emergencies.Materials & Methods:In the cross-sectional study in 2019, 60 senior dental students at the University of Medical Sciences of Isfahan were evaluated. A questionnaire was used for data collection with confirmed validity and reliability. Data was analyzed with correlation coefficients and independent t-test with level of significance at 0.05.Results:Participants' overall knowledge scores were 7.53 ± 2.58out of 12. There wasn't a significant difference between the knowledge of male and female students (p value = 0.72). Also this study revealed a relative relationship between students' medical emergencies score and their knowledge on emergencies (p value < 0.001, r = 0.48).Conclusion:The knowledge status of senior dental students on medical emergencies was not desirable. It is recommended that more educational content like theoretical classes and practical workshops should be considered for dental students